A eficiência dos poleiros artificiais como intensificadores das chuvas de sementes em uma área degradada do cerrado brasileiro - Gomes, Marcia da Silva (2024)
This study focuses on restoring a degraded area within the Avaré Settlement in Santa Rita do Pardo/MS, employing artificial perches as a nucleation technique, which is cost-effective, making it even more accessible and viable for environmental restoration. The objective is to evaluate the effectiveness of these perches in facilitating the arrival of seeds and propagules, aiming to create diversity islands and strengthen the ecological recovery process. We highlight the relevance of this work by emphasizing the need for innovative and sustainable approaches to preserve and restore Cerrado ecosystems, playing a significant role in the protection of this biome.